The use of cloud computing services by Portuguese’s Small and Medium Enterprises (SMEs) : a study which aims to understand to what extent are Portuguese’s SMEs managers using and managing cloud computing services - Duarte, Diogo Miguel de Abreu (2012)
The objective of this dissertation is to understand to what extent are the Portuguese SMEs using and managing Cloud Computing services. This work strives to understand if the managers of the Portuguese SMEs are knowledgeable to embrace this technology, and identify which areas of the Portuguese SMEs’ value chain is Cloud Computing being currently applied and which areas are expected to be explored in the future. In order to address the main objective of this dissertation, an on-line questionnaire is made to several Portuguese SMEs from different economic sectors. This questionnaire has been made by taking into account the knowledge of the Literature Review and the expertise and experience of a pool of experts on the field of Cloud Computing. With the objective of interpreting the data from the on-line questionnaire, a statistical analysis is performed. This data is analyzed trough descriptive statistics, as well as cross-tabulations between variables, according to the research objectives of this work The results of this work highlights that only around 40% of the Portuguese SMEs are using Cloud Computing services consciously, meaning that there are companies using this technology without even being aware of it. According to this study, 73% of the Portuguese SMEs are using Cloud Computing applications without realizing, which consequently means that only 27% of the SMEs do not actually use any kind of Cloud Computing applications. Moreover, the majority of the companies which use this technology are able to identify Cloud Computing most important features as its characteristics, advantages and potential risks. Finally, regarding the Service and Deployment models used by these companies, these are mainly focused on the IaaS and Private Cloud solutions. Nevertheless, most of these companies’ managers still do not see Cloud Computing services as a core technology to use on their primary activities nor use the most appropriate management procedures for the management of this technology (as for example SLAs or KPIs). Consequently, this dissertation’s results show that there is still a long way to go regarding the utilization of Cloud Computing by the Portuguese SMEs.